ONGs brasileiras : práticas assistencialistas ou de defesa dos direitos das crianças? - Oliva, Karla Katherine Arismendi (2020)
This study has as central theme the assistance practices of the socio-educational nongovernmental organization “Associação Amor e Vida”, in order to understand the methodologies used for the children and young people who attend to the project. It is a case study, with a qualitative approach, under a participant observation. Therefore, the objective is to analyze the project's vision / mission in opposition to the needs of the children and young people attending to the center, thus examining the dynamics and / or values that the young people and children who attend the NGO highlight as fundamental, intending to the effectiveness of methodological practices, based on the mission - vision of the NGO, understanding the influence of the educators have on the view that children have of themselves and their surroundings. In this sense, it aims to achieve new practices, coming from to the civil society and political society. To achieve the objectives, semi-structured individual interviews were conducted with five children and five project employees. The research will be carried out based on the concept of popular education by Paulo Freire, based on the proposal that education has to be with the student and not for them, which is the central axis of the project worked on. As it is a socio-educational NGO that serves children and adolescents, during the investigation, topics such as childhood, children and youth, and the changes they have had over the years in relation to state rights, care and state policies, transfer of responsibilities of the State and its impact on the outsourcing of society, and how the latter has a leading role in the creation of NGOs. The results obtained had an emphasis on providing answers to the guiding question of this research and were organized based on final considerations which are argued based on the testimonies collected in the interviews, in this sense, in spite of the NGO's original and religious missionary proposal that advocates a citizen's educational formation, these are social assistance educational measures.